Blasphemy and Protection of the Faith: Legal Perspectives from the Middle Ages - Tolan, John Victor (Islam and Christian-Muslim relations, 2016)
Jewish, Christian, and Muslim legal traditions have all attempted to define and prohibit blasphemy: insult or verbal attack against their religion, against its rites and symbols, against God and his human representatives. Such laws could be internal (prohibiting blasphemy by members of the faith group) or external (prohibiting insult by those outside the faith). This article will first briefly trace the former, looking at how Jewish, Christian, and Muslim legal traditions from Antiquity and the Middle Ages define and prohibit blasphemy. The second part of the article will then focus on the second issue, looking at how Christian and Muslim legal traditions attempted to prohibit insults to the faith by adherents of other religions. We shall look, for example, at various Christian laws dealing with what was perceived as Jewish mockery of Christian ritual and sacred objects: from mock crucifixions allegedly practiced by Jews as part of Purim celebrations in the fifth-century Roman Empire to Jews who supposedly derided the Eucharist during thirteenth-century Corpus Christi processions. We shall in parallel examine prohibitions in Muslim legal texts (including the so-called Pact of ʿ‘Umar) of dhimmīs insulting the Prophet Muhammad or the Qur'an. This comparison will show that, while blasphemy was illegal and could be harshly sanctioned and there were lines that religious minorities must not cross, these lines were often not clearly delimited, and became the object of conflict and negotiation.